Host resistance in black pepper (Piper nigrum L.) against root-knot and burrowing nematode - J. Eapen, Santhosh; Ramana, K.V.; Saji, K.V. (Journal of Plantation Crops, 2011)
Crop resistance is a low-cost option for nematode control in subsistence agriculture and is most useful for low value crops which cannot support the cost of expensive pest management inputs. In this study an attempt has been made to screen the black pepper germplasm to locate resistance/tolerance to burrowing and root-knot nematodes. The germplasm materials collected from the field gene bank of Indian Institute of Spices Research were multiplied in a greenhouse under disease-free conditions for using in the screening studies. In the preliminary screening, 525 black pepper germplasm accessions including 100 wild, 213 each cultivated and 212 hybrids were screened against burrowing nematode. Out of these, 24 accessions showed resistance to R. similis which was confirmed by repeated inoculations. Similarly 431 black pepper accessions were inoculated with M. incognita. Sustainable resistance was observed in only 27 black pepper accessions. Out of these nine black pepper accessions were evaluated under field conditions for five years. All the R. similis-resistant lines viz. Hp 39, Acc. 820 (IC No. 316481), Acc. 1047 (IC No. 316602) and Acc. 1204 (IC No. 316690) were free from nematode infestation initially for two to three years. However, R. similis infection was noticed in all these lines subsequently, which has to be investigated further. However, among the short-listed root-knot nematode resistant lines only two accessions, Acc.1047 (IC No. 316602) and Acc. 1090 (IC No. 316635) were healthy and free from root-knot nematode infestation even after seven years of field planting. In the field evaluation trial, the highest yield was noticed for Acc. 820 and Hp 39.